Step * 2 1 of Lemma satisfies-gcd-reduce-eq-constraints


1. : ℕ+
2. eqs {L:ℤ List| ||L|| n ∈ ℤ}  List
3. sat {L:ℤ List| ||L|| n ∈ ℤ}  List
4. xs {L:ℤ List| ||L|| n ∈ ℤ
5. (∀as∈sat.xs ⋅ as =0) ∧ 0 < ||xs|| ∧ (hd(xs) 1 ∈ ℤ)
⊢ (↑isl(gcd-reduce-eq-constraints(sat;eqs)))
 (∀as∈outl(gcd-reduce-eq-constraints(sat;eqs)).xs ⋅ as =0)
 (∀as∈eqs.xs ⋅ as =0)
BY
-1 }

1
1. : ℕ+
2. eqs {L:ℤ List| ||L|| n ∈ ℤ}  List
3. sat {L:ℤ List| ||L|| n ∈ ℤ}  List
4. xs {L:ℤ List| ||L|| n ∈ ℤ
5. (∀as∈sat.xs ⋅ as =0)
6. 0 < ||xs|| ∧ (hd(xs) 1 ∈ ℤ)
⊢ (↑isl(gcd-reduce-eq-constraints(sat;eqs)))
 (∀as∈outl(gcd-reduce-eq-constraints(sat;eqs)).xs ⋅ as =0)
 (∀as∈eqs.xs ⋅ as =0)


Latex:


Latex:

1.  n  :  \mBbbN{}\msupplus{}
2.  eqs  :  \{L:\mBbbZ{}  List|  ||L||  =  n\}    List
3.  sat  :  \{L:\mBbbZ{}  List|  ||L||  =  n\}    List
4.  xs  :  \{L:\mBbbZ{}  List|  ||L||  =  n\} 
5.  (\mforall{}as\mmember{}sat.xs  \mcdot{}  as  =0)  \mwedge{}  0  <  ||xs||  \mwedge{}  (hd(xs)  =  1)
\mvdash{}  (\muparrow{}isl(gcd-reduce-eq-constraints(sat;eqs)))
{}\mRightarrow{}  (\mforall{}as\mmember{}outl(gcd-reduce-eq-constraints(sat;eqs)).xs  \mcdot{}  as  =0)
{}\mRightarrow{}  (\mforall{}as\mmember{}eqs.xs  \mcdot{}  as  =0)


By


Latex:
D  -1




Home Index